[OP.5D.01] INHIBITON OF TNF-ALPHA SIGNALLING USING ETANERCEPT IMPROVES DEFICIENT UTERINE ARTERY REMODELLING AND PREGNANCY OUTCOME IN THE STROKE PRONE SPONTANEOUSLY HYPERTENSIVE RAT. (September 2016) - SMALL, H.; Nosalski, R.; Morgan, H.; Beattie, E.; Guzik, T.; Graham, D.; Delles, C.
Abstract : Objective: Impaired vascular remodelling has been extensively studied in pre-eclampsia but little is known about adaptation of the cardiovascular (CV) system to pregnancy in women with chronic hypertension. We have previously characterised the stroke prone spontaneously hypertensive rat (SHRSP) as a model of deficient uterine artery remodelling and identified an increase in pro-inflammatory TNF α relative to the normotensive WKY strain during pregnancy. Design and method: SHRSP were treated with etanercept (0.8 mg/kg) or vehicle at gestational day (GD) 0, 6, 12 and 18. Animals were sacrificed at GD18. SHRSP, SHRSP treated with etanercept (ETN) and WKY (n=6) were used for vascular studies. An independent set of animals (n = 6) were used for flow cytometry analysis. Results: Etanercept significantly reduced systolic blood pressure in the SHRSP after GD 10 (δSBP GD 10–21 SHRSP 12.0 ± 4.17 vs. ETN 25.8 ± 4.27 mmHg; p < 0.05). Characterisation of uteroplacental blood flow using Doppler showed that etanercept significantly increased uterine artery diastolic blood flow and significantly reduced resistance index relative to SHRSP (SHRSP 0.79 ± 0.02 vs. ETN 0.61 ± 0.02 resistance index; p < 0.01). Analysis of GD18 uterine arteries using pressure and wire myography showed that etanercept did not change the size of the uterine arteries; but significantly reduced uterine artery contractile ability (SHRSP 57.3 ± 8.75 vs. ETN 35.2 ± 2.19 kPa; p < 0.01) and increased carbachol response (SHRSP 13.8 ± 3.8 % vs. ETN 40.1 ± 3.25 %; p < 0.05). Etanercept significantly increased litter size in the SHRSP (SHRSP 7.80 ± 0.44 vs. ETN 12.75 ± 0.94 fetuses), reduced resorption frequency (SHRSP 66.7% vs. ETN 25.0% dams with resorption) and decreased premature glycogen cell loss from the placenta. We sought to identify the source of excess TNFα in the SHRSP. Inflammatory natural killer (NK) cells (CD3- CD161+) were significantly increased in the SHRSP relative to the WKY in the placenta (WKY 11.6 ± 2.39 vs. SHRSP 659.8 ± 201.2 cells/mg; p < 0.01). Etanercept significantly reduced the number of NK cells in the placenta of the SHRSP (SHRSP 659.8 ± 201.2 vs. ETN 148.0 ± 12.62 cells/mg; p < 0.01). Conclusions: Etanercept improves abnormal uterine artery function in the SHRSP with beneficial effects on pregnancy. Excess TNFα production in this model may come from increased inflammatory NK cells.